Pengaruh Kualitas Produk dan Pelayanan Terhadap Kepuasan Konsumen Pada Rumah Makan Mie Kocok Geurugok (MIKOG) - Ayi Nurfajryah; Riandani Rezki Prana (CIVITAS: Jurnal Studi Manajemen, 2022)
The purpose of this research is to know how much influence product quality and service to customer satisfactionat rumah makan mie kocok geurugok (MIKOG). The sample are 115 consumers who came more than twice in October 2019, using selected sample technique (purposive sampling), which is a sampling technique with certain considerations. Data analysis using multiple regression test, hypothesis testing using the coefficient of determination (R2), partial test (t test), and a simultaneous test (F test), data processing using SPSS 20. Results showed that of variable product quality and service are able to explain the existence of the variable customer satisfaction, besides the partial product quality has no effect and does not significantly influence to customer satisfactionand service have positive and significant influence on customer satisfaction, simultaneous product quality and service have positive and significant impact to customer satisfaction.